SISTEM INFORMASI PEMETAAN BTS DAN KONSUMEN PADA PENYEDIA LAYANAN AKSES INTERNET PT. PROGRESSIO DATAWAVE CAKRAWALA DI KOTA PONTIANAK BERBASIS WEB - Pratiwi, Resmi (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
Abstract-Geographic Information System (GIS) is aÂ  system based on a computer that have the ability in handles data geography. PT. Progressio Datawave Cakrawala is a company that provides the service of internet access in the city of pontianak.As a company that moves in the fields of the internet was supposed to have the the information system mapping bts and consumers that on based of the web. On information systems mapping it can display a radius of a BTS and having information the signal strength and be able to manage data bts and consumers.Testing done with two methods is black box and user acceptance test ( uat ).Testing the black box used to do our tests on the performance programs and uat used to do our tests against the quality of the web being.The result of uat said that the the information system designed able to reach the goal that is, could mapquest bts and consumers and can give information about the strong and the weak a signal from one of BTS which PT. Progressi Datawave Cakrawala.